Co-expression of xerophyte Zygophyllum xanthoxylum ZxNHX and ZxVP1-1 confers enhanced salinity tolerance in chimeric sugar beet (Beta vulgaris L.) - Wu, Guo-Qiang; Feng, Rui-Jun; Wang, Suo-Min; Wang, Chun-Mei; Bao, Ai-Ke; Wei, Li; Yuan, Hui-Jun (Frontiers in Plant Science, 2015)
Salinity is one of the major abiotic stresses that limit the growth and productivity of sugar beet (Beta vulgaris L.). To improve sugar beet’s salinity tolerance, the ZxNHX and ZxVP1-1 genes encoding tonoplast Na+/H+ antiporter and H+-PPase from xerophyte Zygophyllum xanthoxylum were co-expressed by Agrobacterium tumefaciens-mediated transformation. It is showed here that co-expression of ZxNHX and ZxVP1-1 confers enhanced salinity tolerance to the transformed sugar beet plants compared with the wild-type (WT) plants. The chimeric plants grew well in the presence of high salinity (400 mM NaCl), whereas WT plants displayed chlorosis and died within 8 days. Compared to WT plants, the chimeric plants co-expressing ZxNHX and ZxVP1-1 accumulated more proline, Na+ and K+ in their leaves and petioles when exposed to high salinity, which caused lower solute potential, retained more water and thus subjected to lesser cell membrane damage. Interestingly, the chimeric plants accumulated higher sucrose, glucose and fructose contents in their storage roots than WT plants in the absence or presence of high salinity. Our results suggested that co-expression of ZxNHX and ZxVP1-1 improved the osmoregulatory capacity in chimeric sugar beet through increased compartmentalization of ions into the vacuoles by enhancing the activity of proton pumps and thus mitigated Na+-toxicity for plants.